Simplex optimization of a programmed temperature capillary gas chromatographic separation - Lanças, Fernando M.; Francelin, Roseli A. [UNESP]; de Souza, Ailton J. [UNESP] (Wiley, 1991)
The modified simplex algorithm proposed by Nelder and Mead has been used to optimize the separation by temperature programmed capillary GC, of volatile compounds present in alcoholic beverages. An adequate objective function, CRF, based on the separation factor of Kaiser has been used for the optimization process. A factorial design was initially performed to verify the relationship between the several parameters of interest. Following this, the optimization was executed and a surface adjusted within the set of experimental data. Copyright © 1991 Dr. Alfred Huethig Publishers
Keywords: Analysis of volatiles; Capillary gas chromatography (CGC); Multicomponent separation optimization; Simplex optimization; Temperature programmed CGC